GURU SPRITUAL PERLUKAH - Hasibuan, Armyn (AIN Padangsidimpuan, 2016)
Spiritual teacher has two words, namely the person who works the teacher and spirituality. Most experts give a more specific definition, as in a dictionary says that teachers are professional educators in the school with the main task of teaching. The first defenition has more common than the two that has led to formal school teachers. While the first defenition teachers could be outside the formal school, for example, at institutions of non-formal education in the community of origin only he really teaches people so that they know about something in order to be applied or practiced. Spiritual means spirit or spirituality. Spirituality is dipped again at the level of the spiritual sciences Deity in fact much studied by Sufism congregation. The problem, it is necessary spiritual teacher and how its role in improving the understanding of monotheism, especially as a leader in Sufism congregation.